Damage control laparotomie u tupého poranení bricha - Vyhnánek, Frantisek; Duchác, V; Skála, P (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2009)
PURPOSE OF THE STUDY: Damage control surgery is one of the major advances in surgical techniques used in polytrauma patients in the past 25 years. It is based on a foreshortened pre-operative examination during ongoing resuscitation which includes surgical intervention in an injured patient with severe hypotension due to haemorrhage. In this seven-year retrospective study the authors evaluate the results of damage control laparotomy in patients with injury to the abdominal organs, retroperitoneum and pelvis. MATERIAL AND METHODS: The evaluated group included 21 patients with blunt abdominal trauma who underwent damage control laparotomy in the 2001-2007 period. There were 17 men and four women; the age range was 17 to 69 years, with an average of 36 years. Damage control laparotomy was indicated in the patients with blunt abdominal trauma, or with closed or open pelvic fracture, who developed a progressive haemorrhagic shock. RESULTS: Between 2001 and 2007, a total of 21 922 patients were admitted to the Trauma Centre and 12 392 operations were performed. However, only in 21 of them (0.1 %) damage control laparotomy was indicated. The procedure was most frequently performed for liver injury (16 patients), which was associated with multiple injury to the other abdominal organs and retroperitoneum in five patients. Further three patients were operated on for haemoperitoneum at continual bleeding due to type C fracture of the pelvis. In the remaining two patients the damage control procedure was chosen to stop persistent bleeding following splenectomy and nephrectomy for traumatic rupture. In these 21 patients blunt trauma was part of polytrauma (ISS > 15). Repeat surgery was carried out within 48 to 96 hours (average, 58 h). Four patients (19 %) died; two due to progressive traumatic haemorrhagic shock and two because of brain oedema after concussion. DISCUSSION: Damage control surgery has become a fundamental component of surgical strategy for severe trauma and has been accepted by surgeons although it cannot be evaluated in randomized clinical studies. Survival after damage control laparotomy in serious intra-abdominal injuries involved in polytrauma is reported in relation to the scoring system values (ISS, GCS), but depends, first of all, on blood loss, degree of acidosis and severity of associated injuries, with craniocerebral trauma in the first place. CONCLUSIONS: Damage control laparotomy is an effective procedure in the treatment of severe trauma to the abdominal organs and retroperitoneum in critically injured patients. This time-limited, staged surgical intervention is included in resuscitation of patients with hypothermia, metabolic acidosis and coagulopathy. The outcome of damage control surgery is related to not only the severity of injury, but also experience with comprehensive acute care in trauma centres.
Keywords: mužské pohlaví; Male; senioři; tupá poranění; Humans; Female; Abdominal Injuries; poranění břicha; Wounds, Nonpenetrating; Laparotomy; lidé; laparotomie; Middle Aged; ženské pohlaví; lidé středního věku; mladiství; Young Adult; Adolescent; mladý dospělý; dospělí; Adult; Aged